PENGARUH PADAT TEBAR TERHADAP PERTUMBUHAN IKAN REDFIN (Epalzeorhynchos frenatum) Effect of Stocking density on the growth rate Redfin fish (Epalzeorhynchos frenatum) - Rewaldy Siregar; Eriyusni Eriyusni; Indra Lesmana (AQUACOASTMARINE, 2015)
Redfin fish is one of an interesting ornamental fish. Intensive cultivation can bedone by optimizing the stocking density. This reasearch aims to determine the effect ofstocking density of redfin fish, on the growth and determine the optimum stockingdensity with an average length is 5,04 cm and an average weight is 1,01 gram. Redfinare used as much as 162 fishes and maintenance container used are 9 aquariums withsize 40 cm x 20 cm x 20 cm and the volume water are 12 liters each aquarium. Duringthe observed, fish are given an artificial feed as much as 5% of body weight per day.Feeding frequency are 3 times a day. The method used is Completely RandomizedDesign with the treatment of stocking density 1 fish/liter (P1), 1,5 fish/liter (P2), and 2fish/liter (P3). Ended treatment showed length P1 5,59 cm; P2 5,49 cm; P3 5,24 cm andweight P1 1,40 gr; P2 1,28 gr; P3 1,15 gr and feed comsumption 409,05 gr. TreatmentP1 shows the best of daily length and weight growth. Treatment P3 shows the lowest ofdaily length and weight growth. Stocking density significantly affected on the dailylength and weight growth rate. Tukey result has showed that the treatment P2 and P3significantly different from P1.Key word: Epalzeorhynchos frenatum, Redfin, Stocking Density, Growth Rate,